Diplopia following sub-tenon’s anaesthesia : an unusual complication - Blum, Robert Alexander; Lim, Lik Thai; Weir, Clifford R. (Dordrecht : Kluwer, 2012)
Diplopia is a rare but well recognised complication following retrobulbar and peribulbar local anaesthesia but it has not been widely reported following sub-tenon's local anaesthesia (STLA). We report on a 76-year-old woman who developed vertical diplopia after left phacoemulsification. She had received a STLA. She had left hypotropia measuring 30 prism diopters for near and distance. She was managed with occlusion but there was no improvement in her findings over 6 months. Ocular motility opinion was then sought and a presumptive diagnosis of inferior rectus fibrosis was made. She subsequently underwent a left inferior rectus recession using adjustable sutures. Postoperatively she had a residual left hypotropia measuring 8 prism dioptres and single vision. Possible causes of inferior rectus fibrosis include muscle damage during traumatic sub-tenon's block or myotoxicity due to local anaesthetic agents. This case highlights the importance of close supervision of inexperienced staff administering regional anaesthetics.